Comparison of production-related responses to hyperinsulinemia and hypoglycemia induced by clamp procedures or heat stress of lactating dairy cattle - J.W. Stewart; A.G. Arneson; M.K.H. Byrd; V.M. Negron-Perez; H.M. Newberne; R.R. White; S.W. El-Kadi; A.D. Ealy; R.P. Rhoads; M.L. Rhoads (Journal of Dairy Science, 2022)
ABSTRACT: Hyperinsulinemia concurrent with hypoglycemia is one of a myriad of physiological changes typically experienced by lactating dairy cows exposed to heat stress, the consequences of which are not yet well defined or understood. Therefore, the objective of this experiment was to separate the production-related effects of hyperinsulinemia with hypoglycemia from those of a hyperthermic environment. Multiparous lactating Holstein cows (n = 23; 58 ± 4 d in milk, 3.1 ± 0.3 lactations) were housed in temperature-controlled rooms and all were subjected to 4 experimental periods as follows: (1) thermoneutral (TN; temperature-humidity index of 65.1 ± 0.2; d 1–5), (2) TN + hyperinsulinemic-hypoglycemic clamp (HHC; insulin infused at 0.3 µg/kg of BW per h, glucose infused to maintain 90 ± 10% of baseline blood glucose for 96 h; d 6–10), (3) heat stress (HS; temperature-humidity index of 72.5 ± 0.2; d 16–20), and (4) HS + euglycemic clamp (EC; glucose infused to reach 100 ± 10% of TN baseline blood glucose for 96 h; d 21–25). Cows were fed and milked twice daily. Feed refusals were collected once daily for calculation of daily dry matter intake, and milk samples were collected at the beginning and end of each period for component analyses. Circulating insulin concentrations were measured in daily blood samples, whereas glucose concentrations were measured more frequently and variably in association with clamp procedures. Rectal temperatures and respiration rates were greater during HS than TN, as expected, and states of hyperinsulinemia and hypoglycemia were successfully induced by the HHC and high ambient temperatures (HS and EC). Feed intake differed based upon thermal environment as it was similar during TN and HHC periods, and declined for HS and EC. Milk production was not entirely reflective of feed intake as it was greatest during TN, intermediate during HHC, and lowest during HS and EC. All milk components differed with the experimental period, primarily in response to the thermal environment. Interestingly, TN baseline glucose concentrations were highly correlated with the change in glucose from TN to HS, and were related to glycemic status during HS. Furthermore, although few in number, those cows that failed to become hypoglycemic during HS tended to have a greater reduction in milk yield. The work presented here addresses a critical knowledge gap by broadening our understanding of the physiological response to heat stress and the related changes in glycemic state. This broadened understanding is fundamental for the development of novel, innovative management strategies as the dairy industry is compelled to become increasingly efficient in spite of global warming.